ASYMBIOTIC GerminaTION OF the GENUS Cattleya IN DIFFERENT NUTRITIVE MEDIA - MELO, GEMIMA MANÇO DE; PAULINO, PATRÍCIA MARIA DE SOUZA; WILLADINO, LILIA GOMES; CAMARA, TEREZINHA RANGEL; ULISSES, CLÁUDIA (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2015)
Among the Brazilian orchids, the genus Cattleya has a great accent, due to the size and gorgeous coloring of its flowers. Given the different nutritional requirements of each genotype, the present work evaluated the MS and Knudson media, full and half ionic strength, with the intention to observe the germination of the species Cattleya labiata Lindley and the hybrids, Cattleya violacea estriata pedrinho x Cattleya violacea pedrinho and Cattleya violacea pedrinho x Cattleya violacea H21/06-142. In the experiment, the germination was tested in vitro, being evaluated seed viability and the percentage of germination. The triphenyl tetrazolium chloride showed a viability of 70% in the seeds of C. labiata and 95% for the hybrids. It was observed that for the species C. labiata, the nutrient media that provided higher germination percentage were the MS and Knudson media with half of the concentration of salts and to the hybrids, independent of concentration, the MS was more effective, showing superiority over Knudson.